2009
DOI: 10.1002/jmri.21702
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐contrast MRI‐based elastography technique detects early hypertensive changes in ex vivo porcine aortic wall

Abstract: Purpose: To measure the elastic properties of ex vivo porcine aortas in control and hypertensive groups using a phase contrast magnetic resonance imaging (MRI)-based elastography technique. Materials and Methods:Female domestic pigs were randomized to a normal control group (N; n ϭ 5) or a renovascular hypertension group (HT; n ϭ 5) for the duration of 3 months. Mean arterial pressure was significantly higher in the hypertension group than in the control group (173 Ϯ 12 vs. 115 Ϯ 11 mmHg, P Յ 0.05). The animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 20 publications
2
30
1
Order By: Relevance
“…MRE-derived aortic stiffness used in this study is based on the waveguide principle which was previously validated 24, 25, 27, 29 . This principle justifiably allows estimating aortic stiffness by considering waves propagating in the lumen along with the aortic wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRE-derived aortic stiffness used in this study is based on the waveguide principle which was previously validated 24, 25, 27, 29 . This principle justifiably allows estimating aortic stiffness by considering waves propagating in the lumen along with the aortic wall.…”
Section: Discussionmentioning
confidence: 99%
“…MRE has also been used to detect liver tumors 21 , brain tumors 22 , and Alzhemiers 23 . MRE has recently been successfully applied invivo to measure the stiffness of the human aorta 24-27 and also in animals, which are validated against ex-vivo mechanical testing 28 , histopathology 29 and PWV 24, 27 . Additionally, it was also shown that aortic MRE was reproducible in normal healthy volunteers 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance elastography images the propagation of harmonic, low frequency, mechanical shear waves (Muthupillai et al, 1995). Arterial wall stiffness has been extracted using the MoensKorteweg equation (Woodrum et al, 2006) and been applied to ex-vivo porcine aortas (Woodrum et al, 2009;Xu et al, 2012) and in-vivo abdominal aortas (Xu et al, 2013). The phase gradient inversion has identified changes in hypertensive aortic stiffness (Kolipaka et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An invasive method using endovascular imaging catheters was first implemented to perform vascular elastography 11 . Vascular elastography was then achieved using USE, MRE, and OCE [12][13][14] . However, each of them suffers certain limitations.…”
Section: Introductionmentioning
confidence: 99%